中国和英国子宫内膜异位症患者的发病相关因素分析 [Analysis of the factors contributing to endometriosis in China and UK] - Weizhe, NIE; Shuting, LI; Zondervan, KT; Becker, CM; Guo, Y; Zong, L (Editorial of Southern Medical University, 2022)
目的 研究子宫内膜异位症发病的相关因素及其在中国和英国患者之间可能的差异。方法 采用病例对照研究方法，选取英国牛津John Radcliffe Hospital收治的子宫内膜异位症患者387例和非子宫内膜异位症患者199例、广州中医药大学第一附属医院收治的子宫内膜异位症患者101例和非子宫内膜异位症患者50例分别为病例组和对照组。通过标准化的WERF EPHect调查问卷，收集4组人群的身高、体质量、体质量指数、婚姻状况、工作状况、月经情况、生育情况、手术原因等临床资料并进行统计分析。结果 多因素Logistic回归分析结果显示，英国患者中体质量指数、因痛经进行手术、怀孕史、既往子宫内膜异位症手术次数、工作情况等均与子宫内膜异位症的发生相关（P<0.05），而中国患者中痛经史与子宫内膜异位症的发生相关（P<0.05）。结论 痛经可能是中国和英国子宫内膜异位症患者最主要的相关因素；同时，子宫内膜异位症发生的相关因素在中国和英国患者之间可能存在差异. [Objective: To explore the differences in the factors associated with endometriosis between Chinese and British patients. Methods: This case-control study was conducted in 387 patients with endometriosis and 199 non-endometriosis patients admitted to John Radcliffe Hospital (Oxford, UK) and in 101 patients with endometriosis and 50 non-endometriosis patients admitted in the First Affiliated Hospital of Guangzhou University of Chinese Medicine. The clinical data including height, weight, body mass index, marital status, employment, menstruation, fertility, and operation reasons were collected via a standardized WERF EPHect questionnaire. Results: Multivariate logistic regression analysis indicated that body mass index, surgery for dysmenorrhea, history of pregnancy, counts of previous surgeries for endometriosis and status of employment were all significantly associated with endometriosis in the UK (P<0.05), while a history of dysmenorrhea was significantly correlated with endometriosis in Chinese patients (P<0.05). Conclusion: Dysmenorrhea may be the most important common factor associated with endometriosis in China and the UK, but the other factors contributing to endometriosis may differ between these two countries.]